Chronotopic information interaction: integrating temporal and spatial structure for historical indexing and interactive search. (23rd November 2020) - Adams, Benjamin
Abstract: Domain-based learning and research are important applications driving the development of exploratory search systems. A wealth of historical information about events from around the world resides within documents on the web, yet contemporary search engines do not take advantage of the closely integrated temporal and spatial information found within these web pages for indexing and design of search user interfaces. This gap limits the use of the web as a resource for historical and geohistorical information seeking. In this article, we propose chronotopic information interaction as a new interaction concept for web search that explicitly links temporal and spatial entities to keywords using a space–time grid index and a paired search user interface. The space–time grid index allows different modes of interaction between spatial, temporal, and keyword-based views in the search user interface. We demonstrate the use of the space–time grid index and chronotopic information interaction concept with the development of Pteraform, a prototype of a search engine that enables users to explore information in the English version of Wikipedia through a geohistorical lens.